(untitled) (Forum Penelitian Agro Ekonomi, 2013)
Food reserve is essential in stabilizing domestic food supplies. According to the Law No. 18/2012 on Food, national food reserve system should meet two principles, namely: (1) the reserve should be mainly built upon the national food production, and (2) the reserve is a multi-layer reserve system. Since there are diversified local food sources, the national food reserve system can be functioned as sources of diversified food supplies for the society. Indonesia needs to build a robust and resilience national food reserve due to increases in threat of global food crisis, volatility of global food supplies and prices, risks of natural disasters, and relatively large numbers of food insecure people. Indonesia adopts the stock based on the utilization ratio method in determining the Government Rice Reserve. It is advisable to harmonize quantities and kinds of food reserves managed by Central Government, Local Governments, private sector, and community.